Evaluation of bacterial pathogens and their antibiotic resistance on surfaces in the Mohammed V hospital, Al-Hoceima, Morocco - Abourrich, Mostapha; Mourabit, Nadira; El Barghmi, Rachida; Boussa, Samia; Ghalit, Mohammed; El Ouarghi, Hossain (The Journal of Infection in Developing Countries, 2025)
Introduction: The hospital environment is an important source of nosocomial infections. Surfaces in the hospital facilities may be considered as microbial reservoirs that can cause patient contamination. This study aimed to evaluate the microbiological quality of surfaces and equipment in the Mohammed V Hospital, located in Al-Hoceima, Morocco. Methodology: A total of 360 samples of surfaces were collected by swabbing from 5 service departments (intensive care unit (ICU), maternity, neonatology, operating room, and pediatric) over a period of 1 year (January–December 2021). The samples were analyzed at the provincial public health laboratory of Al-Hoceima. Isolation and identification of bacteria were performed according to conventional bacteriology methods. Results: The results indicated that 34.4% (124/360) samples were contaminated. The ICU was the most contaminated service and the frequency of contaminated samples was 50%. The most contaminated sampling sites were soap for hand washing (27.4%), trolleys (25.8%), and sinks (22.6%). Gram-positive bacteria represented 51.6% of the contaminants. The most isolated bacteria were Staphylococcus aureus (50%), followed by Klebsiella pneumoniae (23.5%), and Pseudomonas aeruginosa (12.4%). Extended spectrum beta lactamase-producing Enterobacteriaceae represented 31.7% of the contaminants. Methicillin-resistant Staphylococcus aureus (MRSA) accounted for 17.6% of the contaminants. Conclusions: This study provided important data that can guide the nosocomial infection control committee to manage the risks related to contaminated hospital surfaces through the establishment of an adequate risk analysis strategy.